Characterization of Cd and As accumulation and subcellular distribution in different varieties of perennial ryegrasses - Li Cao; Na Jiang; Bo Li; Jiangdi Deng; Yumo Duan; Yanqun Zu; Zuran Li (BMC Plant Biology)
Abstract Background The distribution, accumulation, and toxicological effects of two perennial ryegrass (Lolium perenne L.) varieties under combined cadmium (Cd)-arsenic (As) stress are worth exploring. Two varieties, ʻNicaraguaʼ (high-Cd/As-accumulating, DPB) and ʻVenusʼ (low-Cd/As-accumulating, WNS), were selected as experimental materials for pot trials. Subcellular fractionation, ultrastructural changes, and key transporter proteins cation exchanger (CAX), heavy metal ATPase (HMA), natural resistance-associated macrophage protein (NRAMP), and phosphate transporter (PHT) were analyzed under combined Cd-As stress. Results (1) The translocation factors of perennial ryegrass for Cd and As were < 1. Cd and As were mainly distributed in the cell wall and the soluble fractions. The total percentage of Cd and As in the cell wall and the soluble fractions of DPB variety was 92.53 and 91.29%, respectively. (2) Cd and As stress on the cellular ultrastructure of two perennial ryegrasses resulted in plasmodesmata separation of leaf cells, swelling of chloroplasts, large numbers of osmiophilic granules, and thickening of root cell walls. Cell wall thickening was more pronounced in the low-accumulating variety. (3) The highest increase in HMA activity, which increased by 79.08% over the non-Cd/As treatment, was observed in the roots of DPB under Cd and As stress. Cd and As stress induced HMA activity (P < 0.01) in the highly accumulating variety DPB, and positively promoted Cd translocation and storage in the soluble fraction (vacuole). Conclusions Low Cd accumulation variety mainly resisted heavy metal through bound more Cd and As to cell wall resulting in cell wall thicken. High-Cd accumulation variety DPB stored Cd and As in the soluble fraction (vacuole ), and enhanced activity of the transporter protein HMA. This study elucidates the relationship and role of key transporter proteins of high/low accumulating perennial ryegrass with cellular Cd/As detoxification modes such as cell wall barrier defence and vesicle compartmentalisation, and provides a theoretical basis for differential detoxification strategies for species with different accumulating characteristics. Graphical Abstract